PERILAKU PEDAGANG PASAR SENIN DAN PASAR MODREN DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Indri Ariyani; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at the Monday Market and Modern Market, Pasir Pengaraian City, Rokan Hulu Regency. The problems studied are about how the behavior of the Monday Market and Modern Market traders in Rambah District, Rohul Regency as well as the factors that influence the behavior of traders in the Monday Market and Modern Market. In selecting research subjects, it was done by setting certain criteria (purposive sampling). For the data collection process, the authors used interview guidelines and conducted in-depth interviews with all research subjects with the aim of obtaining valid data. The results in this study explain that the behavior of Pasar Senin traders in setting prices is in accordance with the standard, and there will be additional products if there are purchases in sufficient quantities. Meanwhile, the behavior of the Pasir Pengaraian Modern Market traders does not add products if there are purchases in large quantities. The behavior of Pasar Senin traders in setting prices is in accordance with the standard, and there will be additional products if there are purchases in sufficient quantities. Traders at Pasar Senin and Pasar Modern Pasir Pengaraian maintain product quality, but traders at Pasar Senin still offer products that have decreased in quality.       Keywords: Behavior, Traders, Market, Traditional, Modern